Cyprus mothers׳ breast feeding self-efficacy and their perceptions about the implementation of the ‘10 steps’ in the first 48 hours after birth - Hadjiona, Vasiliki; Middleton, Nicos; Kouta, Christiana; Hadjigeorgiou, Eleni; Lambrinou, Ekaterini; Kolokotroni, Ourania (My University, 2016)
Background :more than two decades after the launch of the ‘10 steps’ for successful breast feeding, there is still concern that implementation is suboptimal. Commonly, studies assess the level of implementation based on self-assessments from maternity staff and more rarely based on the mothers’ own experience. To date, there has been only anecdotal evidence with regards to the implementation of the ‘10 steps’ in Cyprus while there is general lack of research data on breast feeding in this country.Aim:this study assessed breast feeding self-efficacy among mothers during the first 48 hours after birth and explored their views with regards to the implementation of the ‘10 steps’ across public and private maternity units in Nicosia, Cyprus.Method this is a descriptive study with a consecutive sample of 216 mothers, aged at least 18, who gave birth to a full-term healthy infant between January and April 2014. Two data collection tools were used: Section 4 of the BFHI (Baby Friendly Hospital Initiative) questionnaire referring to mothers’ self-assessment of maternity unit practices and the BSES-SF (Breast feeding Self-Efficacy Scale - Short Form) which measures perceived self-efficacy in bryeast feeding.Results midwifery assistance for breast feeding skills development along with encouragement of breast feeding on demand (steps 5 and 8) were identified by mothers as the steps they were more likely to have experienced. In addition, there appeared to be relatively good adherence to the International Code of Marketing of Breast-milk Substitutes. In contrast, it seems that step 7(rooming-in), step 9 (no pacifiers) and step 10 (breast feeding support after discharge) were not systematically practiced. While a higher percentage of mothers in public maternity units reported being informed about the importance of skin-to-skin contact compared to the private sector (51.5% versus 25.7%), there does not appear to be much difference in terms of its actual practice which is generally low (29.0% versus 25.4%). Exclusive breast feeding (step 6) was low (21.7%) while the mean score of breast feeding self-efficacy at 48 hours was 3.33 (0.87SD) on a 5-point Likert scale.Conclusions it appears that mothers in Cyprus had limited experience of the ‘10 steps’ during their stay Nicosia maternity units. This, along with the fact that exclusive breast feeding and breast feeding self-efficacy were rather low, suggests the need for interventions that will enhance breastfeeding self-efficacy and empower mothers to initiate breast feeding while at the maternity unit. In particular, the limited information to mothers upon leaving the maternity unit highlights the lack of maternal support services in the community.
Keywords: Mothers; Perceptions; Breast feeding; Self-efficacy; Implementation; 10 steps